2018
DOI: 10.1183/13993003.01024-2017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the mitochondria-targeted antioxidant MitoQ on hypoxia-induced pulmonary hypertension

Abstract: Increased mitochondrial reactive oxygen species (ROS), particularly superoxide have been suggested to mediate hypoxic pulmonary vasoconstriction (HPV), chronic hypoxia-induced pulmonary hypertension (PH) and right ventricular (RV) remodelling.We determined ROS in acute, chronic hypoxia and investigated the effect of the mitochondria-targeted antioxidant MitoQ under these conditions.The effect of MitoQ or its inactive carrier substance, decyltriphenylphosphonium (TPP), on acute HPV (1% O for 10 minutes) was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 46 publications
3
64
1
Order By: Relevance
“…The acute and chronic responses of the pulmonary vasculature to hypoxia have hitherto been assumed to involve similar primary mechanisms and to share regulatory components. However, our data point toward different signaling pathways operating in the two conditions and thus support previous studies that demonstrated a different mechanism of acute HPV and chronic hypoxia-induced PH (5,30,36). Confusingly, previous studies have implicated directionally opposite changes in mitochondrial ROS in chronic hypoxia showing both an increase (28) and a decrease in mitochondrial ROS (37) affecting PASMC proliferation and pulmonary vascular remodeling (38,39).…”
Section: Fig 5 Integration Of Present Findings Into Current Conceptsupporting
confidence: 88%
See 2 more Smart Citations
“…The acute and chronic responses of the pulmonary vasculature to hypoxia have hitherto been assumed to involve similar primary mechanisms and to share regulatory components. However, our data point toward different signaling pathways operating in the two conditions and thus support previous studies that demonstrated a different mechanism of acute HPV and chronic hypoxia-induced PH (5,30,36). Confusingly, previous studies have implicated directionally opposite changes in mitochondrial ROS in chronic hypoxia showing both an increase (28) and a decrease in mitochondrial ROS (37) affecting PASMC proliferation and pulmonary vascular remodeling (38,39).…”
Section: Fig 5 Integration Of Present Findings Into Current Conceptsupporting
confidence: 88%
“…There are also contradictory reports on the effects of mitochondrial ROS on HIF-1, which is a major driver for the development of chronic hypoxia-induced PH (39), with some authors finding evidence of its stabilization by ROS (28,40), while others found no such effect (41). Recently, we found evidence for a decrease in PASMC ROS levels in chronic as opposed to acute hypoxia (36). The fact that AOX did not inhibit chronic hypoxia-induced PH, nor interfere with hypoxiainduced stabilization of HIF-1, may help resolve these discordant findings, recasting the acute and chronic effects of hypoxia in lungs as two fundamentally different processes.…”
Section: Fig 5 Integration Of Present Findings Into Current Conceptmentioning
confidence: 65%
See 1 more Smart Citation
“…Interestingly, a divergent regulation of ROS production by PASMCs in acute and chronic hypoxia was previously reported with a significant decrease of ROS production upon acute exposure and a robust increase in ROS levels after chronic exposure [27]. Although additional work is needed to reconcile these discrepant experimental results, PAK et al [14] have brought to light new evidence of the mutual relationship between hypoxia and ROS, fuelling the continuing debate surrounding redox events in pulmonary oxygen sensing. Interesting related questions remain.…”
mentioning
confidence: 86%
“…In their study, PAK et al [14] investigated the open question whether ROS are decreased or increased during acute and chronic hypoxia in the pulmonary vasculature and RV. Using complementary methods, the authors first documented changes in the redox state of mouse PASMCs during acute hypoxia (1% O 2 for 5 min).…”
mentioning
confidence: 99%